Viable Putative Vibrio vulnificus and parahaemolyticus in the Pensacola and Perdido Bays: Water Column, Sediments, and Invertebrate Biofilms - Potdukhe, Trupti V.; Caffrey, Jane M.; Rothfus, Mackenzie J.; Daniel, Carrie E.; Swords, Michael E.; Albrecht, Barbara B.; Jeffrey, Wade H.; Waidner, Lisa A. (Frontiers in Marine Science, 2021)
Vibriosis is the general term for human illnesses caused by infection of pathogenic Vibrio species. Vibrio vulnificus (Vv) and parahaemolyticus (Vp) are two problematic waterborne pathogens that have yet to be enumerated in northwest Florida coastal Gulf of Mexico estuaries. In this regionally novel study, we surveyed 43 locations in two subtropical estuarine systems, Perdido Bay and Pensacola Bay, over seven dates in winter 2020. Sampling included three substrate types: surface waters, sediments, and invertebrate biofilms. We determined baseline abundances of presumptive viable Vv and Vp appearing as colonies on CHROMagar (Vv, blue; Vp, purple). Vv was detected in 37 out of 43 water samples, with maximum levels of 3,556 CFU/mL. Vp was only detected in 15 water samples, with a maximum concentration of 8,919 CFU/mL. Sediments contained Vv in all but one sample, with concentrations ranging from 121 to 607,222 CFU/mL. In contrast, Vp were only detected in 33 sediment samples, where concentrations ranged from 28 to 77,333 CFU/mL. Opportunistically-sampled surface swabs (biofilms), collected from shells (either oyster or barnacle) and polychaete worms found in sediment samples, contained on average 7,735 and 1,490 CFU/mL of Vv and Vp, respectively. Surface water Vv abundances covaried with bottom water pH, maximum prior cumulative wind speeds, and tidal coefficient on the day of sampling. Vp surface water abundances negatively correlated with surface water salinity, surface water pH, and bottom water pH and positively correlated with total surface dissolved inorganic and total Kjeldahl nitrogen concentrations, and wind. Spatially, there was large variation in Vibrio densities in surface waters; abundances of both species were strongly correlated with wind, suggesting resuspension was important. Sedimentary abundances of both putative Vv and Vp shared a correlation with one parameter: salinity stratification. Due to the length of this study, temperature was not considered a major factor. This short-term (1 month) study was designed not to enumerate pathogenic Vv or Vp, but rather to establish the first winter baseline of Vibrio abundances for this region. Determination of these baseline winter cultivable putative Vibrio abundances will be valuable in predicting relative risk factors in each waterbody of interest.